Interventions in increasing availability of skilled healthcare providers in rural areas: A Case Study of Bihar (India) - Kumar, Dilip (Technium Social Sciences Journal, 2021)
Population of rural areas face distinct health challenges due to economic conditions, cultural/behavioural factors, and health provider shortages that combine to impose striking disparities in health outcomes among them. The process of recruitment takes about four to six months for Recruitment of Medical officers and paramedics. The number of applicants is quite limited because of dearth of doctors and paramedics in the State. It was felt that the health staffs incentives will help to increase the turnover of health staffs to some extent in the rural and remote areas. Monitoring cell has been constituted at the state level. The trainings are being monitored at regular intervals of time. The motivational level of health staff at all levels seems to be low. Continuous communication and feedback by state level programme officers is needed on regular basis. Placement of the suitable trained personnel is needed at those health facilities where sufficient infrastructure is available. Since 2010-11, there has been a continuous focus on the capacity building of the existing manpower in the state. Trainings as per GOI guidelines on Immunization, IMNCI, EmOC, LSAS, SBA and Minilap/MVA etc. have been taken up with full strength. In addition, the State wide training on immunization for Medical Officers, IPC skills for breast feeding and basic training in neonatal resuscitation also has been taken up at various levels. More than four-fifth of the total staffs in the health facilities were agreed on all the educational interventions for retention of health staffs in rural areas. For the regulatory interventions such as enhanced scope of practice, different types of health workers; multi skilling of alternate service providers, compulsory rural service which may be mandatory for obtaining license to practice or can be a prerequisite for entry into specialization and subsidized education in return of assured services were agreed by four-fifth of the total staffs. For the interventions related to professional and personal support such as better living conditions (water, sanitation, electricity, telecommunications, schools, etc.), safe and supportive working environment, outreach activities to facilitate cooperation between health workforce from better served and underserved areas; use of tele-health, designing career development programmes linked with rural service: more senior posts in rural areas and professional networks for rural areas such as rural health professional associations, rural health journals, etc. about 88 percent of the HR categories of Staffs were agreed in the health facilities